Birds of a feather? Mis- and dis-information on the social media platform X related to avian influenza - Lauren N. Cooper; Marlon I. Diaz; John J. Hanna; Zachary M. Most; Christoph U. Lehmann; Richard J. Medford (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract